2011
DOI: 10.1128/jb.06356-11
|View full text |Cite
|
Sign up to set email alerts
|

The MagA Protein of Magnetospirilla Is Not Involved in Bacterial Magnetite Biomineralization

Abstract: Magnetotactic bacteria have the ability to orient along geomagnetic field lines based on the formation of magnetosomes, which are intracellular nanometer-sized, membrane-enclosed magnetic iron minerals. The formation of these unique bacterial organelles involves several processes, such as cytoplasmic membrane invagination and magnetosome vesicle formation, the accumulation of iron in the vesicles, and the crystallization of magnetite. Previous studies suggested that the magA gene encodes a magnetosome-directed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 45 publications
0
26
1
Order By: Relevance
“…Although it is tempting to suggest that this could be related to magA ’s function as an iron transporter, leading to more iron uptake and consequently an increase in FTH1 translation, recent evidence suggests that magA is not only unnecessary for magnetosome formation in MTBs but also unlikely to work as an iron transporter. 30 It is now known that iron is not the only regulator of ferritin translation and that other signals, including oxidative stress, can lead to increases in ferritin protein. 32 Considering our observations with stem cells, which did not tolerate the expression of magA , it is reasonable to suggest that magA expression in HEK cells might also lead to changes in homeostasis with one of the consequences being an increase in FTH1 translation.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is tempting to suggest that this could be related to magA ’s function as an iron transporter, leading to more iron uptake and consequently an increase in FTH1 translation, recent evidence suggests that magA is not only unnecessary for magnetosome formation in MTBs but also unlikely to work as an iron transporter. 30 It is now known that iron is not the only regulator of ferritin translation and that other signals, including oxidative stress, can lead to increases in ferritin protein. 32 Considering our observations with stem cells, which did not tolerate the expression of magA , it is reasonable to suggest that magA expression in HEK cells might also lead to changes in homeostasis with one of the consequences being an increase in FTH1 translation.…”
Section: Discussionmentioning
confidence: 99%
“…Although not an essential magnetosome gene (Uebe et al, 2012), we showed that overexpression of MagA from AMB-1 provides MR contrast comparable to the overexpression of modified, mammalian ferritin subunits ( HF + LF ) that are devoid of iron regulatory elements (Rohani et al, 2013). In a mouse model of tumor growth, transplanted cells were repetitively imaged over 5 weeks and compared to the parental cell xenograft.…”
Section: Introductionmentioning
confidence: 90%
“…142 However, magA as a putative MR reporter gene is rather controversial as its implication in magnetosome formation has recently been contested. 169 A second magnetosome gene, Mms6, is being explored as a reporter for MRI contrast. 170 The Mms6 protein has a high affinity for iron proteins 171 and plays a critical role in the crystallization of magnetite within magnetosomes, most probably in controlling the magnetite crystal morphology.…”
Section: Genetic Reporters For Mrimentioning
confidence: 99%